Business Anthropology Broadens Academic Research Paths: Experiences and Insights Gained - Wang, Yanyu (Journal of Ecohumanism, 2025)
This paper looks at how the author, under the guidance of predecessors in business anthropology, continuously broadens academic research paths and masters and applies business anthropology framework and research methodology. First, it summarizes the learning outcomes and methodological mastery of the foundational business anthropology theories. It lays a solid theoretical and methodological foundation for the subsequent in-depth research. Following this, the author elaborates on constructing a logical and innovative dissertation framework under the supervisor’s guidance. It highlights the complete trajectory from conceptualization to finalization of the dissertation, including the logic of thinking and responses to challenges. In addition, it describes how to improve language skills to ensure the rigor of academic research in writing an academic paper. This paper is a summary of the learning experience. It also provides reference and inspiration for researchers interested in business anthropology.